Efeitos dos treinamentos multimodal e mat Pilates na marcha e equilíbrio de pessoas com doença de Parkinson: um ensaio clínico randomizado unicego - Sousa, Lucas Resende (2021)
Background: The clinical manifestations of Parkinson's disease (PD), especially changes in gait and balance, have a direct impact on the performance of daily activities, related to the increased risk of falls. In this context, physical exercise is considered one of the best resources to assist in the treatment of PD. Aim: To evaluate the effects of Multimodal Training (TM) and Mat Pilates (MP) on the gait and balance of people with PD. Methods: Clinical trial of treatment, randomized, single-blind, parallel with two arms, with the participation of 34 people with idiopathic PD in the initial stage and randomly distributed in 2 intervention groups: MP and TM, which were performed in 60-minute sessions, three times a week, for twelve weeks. For gait assessment, spatiotemporal parameters and gait variability were used in a comfortable speed situation, using a 10m walkway and the CHANNELS MYOTRACE 400: BLUETOOTH (Noraxon®) equipment with footswitch pressure sensors. To assess functional mobility, use the Timed Up and Go test (TUG) and double task TUG (TUG DT); and for balance assessment, MiniBESTest was used. To compare the variables in the different evaluation periods, the Generalized Estimating Equation Model (GEE) test was used, adopting a significance level of p <0.05 and to verify the effect size, Cohen's d was used. Results: TM compared to MP promoted a substantial improvement in gait parameters, observed by increasing gait speed, swing time, stride length and stride, decreased cadence and double support time, decreased variability speed, swing time, double support time, step time and single support time. Both interventions promoted an improvement in the MiniBESTest score; only the TM was able to decrease the time to perform the TUG DT; and neither intervention significantly improved the time to perform the TUG. Conclusion: The TM compared to the MP showed superiority both in improving gait performance and in improving balance in individuals with PD.